Switch Reluctance Motor Control Based on Fuzzy Logic System - S. V. Aleksandrovsky; Yu. N. Petrenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
Due to its intrinsic simplicity and reliability, the switched reluctance motor (SRM) has now become a promising candidate for variable-speed drive applications as an alternative induction motor in various industrial application. However, the SRM has the disadvantage of nonlinear characteristic and control. It is suggested to use controller based on fuzzy logic system. Design of FLS controller and simulation model presented.